The characteristic of nonmotor symptoms with different phenotypes and onsets in multiple system atrophy patients. (March 2023) - Zhang, Jinhong; Han, Jiuyan; Shi, Zhihong; Zhang, Jiewen; Zhou, Zhi; Liu, Junyan; Yang, Gaiqing; Sun, Yongan; Gu, Ping; Zhao, Ping; Ma, Lili; Gong, Zhongying; et al.
Abstract: Objectives: The characteristic of nonmotor symptoms in patients with multiple system atrophy (MSA) has varied among previous studies. The objective was to investigate the nonmotor characteristics in MSA patients with different phenotypes, sex and different onset patterns. Methods: We performed a retrospective review of 1492 MSA patients. All cases were evaluated by neurologists and assessed with motor manifestations, nonmotor symptoms, auxiliary examination and brain MRI scans. Results: Multiple system atrophy–cerebellar ataxia (MSA-C) was the predominant phenotype in 998 patients. Average age of onset (56.8 ± 9.2 years) was earlier, the disease duration (2.4 ± 2.2 year) was shorter and brain MRI abnormalities (49.2 %) were more frequently in MSA-C (P < 0.001). Multiple system atrophy–parkinsonism (MSA-P) patients were more likely to have nonmotor symptoms. After adjusted significant parameters, urinary dysfunction (OR 1.441, 95 %CI = 1.067–1.946, P = 0.017), constipation (OR 1.482, 95 %CI = 1.113–1.973, P = 0.007), cognitive impairment (OR 1.509, 95 %CI = 1.074–2.121, P = 0.018) and drooling (OR 2.095, 95 %CI = 1.248–3.518, P = 0.005) were associated with the MSA-P phenotype. Males were more likely to have orthostatic hypotension, urinary dysfunction, sexual dysfunction, drooling and females in constipation and probable RBD. In different onset patterns, constipation (59.2 %) and probable RBD (28.4 %) were more frequently in autonomic onset pattern. Conclusions: MSA-C is the predominant phenotype in Chinese patients, while many nonmotor symptoms are more common in MSA-P phenotype. Patients with different sex and onset patterns have different nonmotor characteristics. The different clinical features identified could help the physician counseling of MSA patients more easily and more accurately.